DIAGNOSTIC VALUE OF SERUM ENZYMES-A REVIEW ON LABORATORY INVESTIGATIONS.: Life Sciences-Bio Chemistry - VIDYA SAGAR; DR. VANDANA BERRY; DR.ROHIT J. CHAUDHARY (International Journal of Life Science and Pharma Research, 2022)
Enzymes are produced intracellularly, and released into the plasma and body fluids, where their activities can be measured by their abilities to accelerate the particular chemical reactions they catalyze. But different serum enzymes are raised when different tissues are damaged. So serum enzyme determination can be used both to detect cellular damage and to suggest its location in situ. Some of the biochemical markers such as alanine aminotransferase, aspartate aminotransferase, alkaline phasphatase, gamma glutamyl transferase, nucleotidase, ceruloplasmin, alpha fetoprotein, amylase, lipase, creatine phosphokinase and lactate dehydrogenase are mentioned to evaluate diseases of liver, pancreas, skeletal muscle, bone, etc. Such enzyme test may assist the physician in diagnosis and treatment.